Dependence of daytime thermospheric winds on IMF By as measured from south pole - Zou, Ying; Sheng, Cheng; Conde, Mark; Shi, Xueling; Bristow, William A.; Wu, Yen-Jung Joanne (Frontiers in Astronomy and Space Sciences, 2024)
Winds in the nighttime upper thermosphere are often observed to mimic the ionospheric plasma convection at polar latitudes, and whether the same is true for the daytime winds remains unclear. The dayside sector is subject to large temperature gradient set up by solar irradiance and it also contains the cusp, which is a hotspot of Poynting flux and a region with the strongest soft particle precipitation. We examine daytime winds using a Scanning Doppler Imager (SDI) located at the South Pole, and investigate their distribution under steadily positive and negative IMF By conditions. The results show that daytime winds exhibit significant differences from the plasma convection. Under negative IMF By conditions, winds flow in the same direction as the plasma zonally, but have a meridional component that is strongest in the auroral zone. As a result, winds are more poleward-directed than the plasma convection within the auroral zone, and more westward-directed in the polar cap. Under positive IMF By conditions, winds can flow zonally against the plasma in certain regions. For instance, they flow westward in the polar cap despite the eastward plasma convection there, forming a large angle relative to the plasma convection. The results indicate that ion drag may not be the most dominant force for daytime winds. Although the importance of various forcing terms cannot be resolved with the utilized dataset, we speculate that the pressure gradient force in the presence of cusp heating serves as one important contributor.